Evaluation of Glycerol Profiles in Sugarcane Spirits (Cachaças) - Garcia,André C. (2015)
A new method for glycerol quantification in sugarcane spirits (cachaças) is proposed, based on sample derivatization using benzoyl chloride followed by solid-phase extraction and high performance liquid chromatography with diode array detection analysis. The limits of detection and quantification for glycerol analysis are 0.25 mg L−1 and 0.74 mg L−1, respectively. The accuracy is of 97.5%, the precision 93.5% and the linearity r2 = 0.998 in the range of 0.56 mg L−1 to 112.0 mg L−1 of glycerol. Experiments with forty eight samples of aged and non-aged cachaças and seven alcoholic extracts of wood showed that the aging process contributes to increase the glycerol concentration. The average concentration of glycerol in aged cachaças were about 10-fold higher than in non-aged cachaças.